Problems and solutions to access to documents in sanction proceedings – judicial ruling in the Competition, Regulation and Supervision Court of Santarém, Portugal. - Baptista, Alexandre Leite (2018)
This article analyzes the recent judicial practice of the Competition, Regulation and Supervision Court in relation to interlocutory measures of the Portuguese Competition Authority, concretized in the interpretation and application of Articles 30 (Business secrets), 31 (Proof), 32 (Publicity of the case and secrecy of justice) and 33 (Access to the process), all of the Novo Regime Jurídico da Concorrência, approved by Lei n. 19/2012, of 08 May, and through the formulation of rules of procedural action in the guarantees of access to documentary evidence in the respective sanctioning process.